2013
DOI: 10.1007/s00705-013-1666-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of a chimpanzee herpesvirus and its relation to other primate alphaherpesviruses

Abstract: Summary This study reports the complete genome sequence of chimpanzee herpesvirus (ChHV), an alphaherpesvirus isolated from a chimpanzee. Although closely related to human herpes simplex virus type 2 (HSV2), the level of sequence diversity confirms that ChHV is sufficiently distinct to be considered a member of a different virus species rather than a variant strain of HSV2. Phylogenetic comparison with other simplexviruses at several levels supports the hypothesis that HSV2 and ChHV co-evolved with their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 5 publications
1
36
0
1
Order By: Relevance
“…We used consensus sequences to generate a whole genome alignment that also included the sequences from all georeferenced simplexvirus genomes determined from hominine hosts, i.e., HSV-1, HSV-2, and the only sequence derived from a chimpanzee (chimpanzee alpha-1 herpesvirus, ChHV; Severini et al 2013), as well as the sequence of the cercopithecine herpesvirus 2 (Tyler et al 2005) (supplementary table S1, Supplementary Material online, p. 2–5). …”
Section: Resultsmentioning
confidence: 99%
“…We used consensus sequences to generate a whole genome alignment that also included the sequences from all georeferenced simplexvirus genomes determined from hominine hosts, i.e., HSV-1, HSV-2, and the only sequence derived from a chimpanzee (chimpanzee alpha-1 herpesvirus, ChHV; Severini et al 2013), as well as the sequence of the cercopithecine herpesvirus 2 (Tyler et al 2005) (supplementary table S1, Supplementary Material online, p. 2–5). …”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the genome of a chimpanzee herpesvirus (ChHV) isolated in 2004 showed that HSV-2 was more closely related to ChHV than to HSV-1 (13,14). Phylogenetic analysis suggested that HSV-2 might be the original human herpes simplex virus (14).…”
mentioning
confidence: 99%
“…Phylogenetic analysis has shown that HSV-2 is more closely related to chimpanzee herpesvirus 1 (ChHV-1) than to HSV-1 (17,18). Until recently, only one genomic HSV-2 sequence of a clinical isolate had been available, but another was made available recently (19,20).…”
mentioning
confidence: 99%